Peningkatan Pemahaman Kitab Kuning Dengan Kaidah Pegon - Ma'rifatul Halimatus (LP3M IAIFA Kediri, 2021)
Islamic Boarding School of Al-Barokah is located in Mangunsuman, Siman, Ponorogo, East Java. This salaf (ancient) Islamic Boarding School based on the yellow book aims to integrate religious science and knowledge-based on ilmiyah 'amaliyah based on Ahlu Sunah wal Jamaah an-Nahdliyah. However, it is unfortunate that the learning process experienced some obstacles due to the lack of santri mastery in the correct use of pegon rules. With the pegon training program, it is expected that santri can improve its understanding of the study of the yellow book. The method used in this devotion is to use the ABCD (Asset Based Community Driven Development) approach described through descriptive qualitative methods. The object of this devotion is a new santriwati numbering 15 people. Evaluation results showed the trainees' abilities improved. This is seen from the reach of the training objectives seen from the results of pre-test and post-test and the ability of participants in mastering the material. There was an 18% increase in the understanding of the kuing book using the correct pegon rules that had been given in training. Of course, a thorough evaluation and assistance is still needed as a follow-up work plan.